Introducing Circular Bio-Economy Innovation Hub in Ghana: Co-ownership for Sustainable Impact Facilitation - CGIAR Initiative on Resilient Cities (CGIAR Initiative on Resilient Cities, 2023)
To mitigate the negative effects of urbanization on resource use and environmental pollution, 15 key actors in the waste-sanitation-agriculture interface joined efforts to set up a Circular Bioeconomy Innovation Hub in Ghana. Based on a decade of CGIAR research, the hub links ministries, universities, science, and private sector, to offer their infrastructure and knowledge for building capacity in circular bio-solutions for school students to professionals. Using co-ownership principles, the hub builds on jointly defined objectives and workplans.